2021
DOI: 10.1001/jamapediatrics.2021.1046
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pregnant Women and Their Newborn Infants

Abstract: employers and consumers that they will likely continue to grow in prominence. Today, too little is known about the effects of HDHPs on the health of children and their use of health care, particularly for children with chronic health conditions. Policy makers must consider further what other components of health care should be exempted from deductibles in HDHPs in an effort to minimize risks and maximize benefits for children enrolled in such plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
1
13
0
3
Order By: Relevance
“…The limitation of the clinical design of the study is that we could not compare the GA and MGO values in a control group matched for obesity and the prevalence of diabetes. However, the interpretation of the data that we are supporting here is greatly supported by the large epidemiological studies on COVID-29 syndrome that found a highly significant association of obesity and diabetes with the severity of SARS-CoV-2 infection [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The limitation of the clinical design of the study is that we could not compare the GA and MGO values in a control group matched for obesity and the prevalence of diabetes. However, the interpretation of the data that we are supporting here is greatly supported by the large epidemiological studies on COVID-29 syndrome that found a highly significant association of obesity and diabetes with the severity of SARS-CoV-2 infection [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 75%
“…It is also of interest that MGO-induced RAGEs play a role in platelet activation [ 14 ], which may lead to additional SARS-CoV-2 infection complications. These metabolic processes are also expressed in control pregnant subjects since pregnancy is characterized by para-physiological dyslipidemia and insulin resistance [ 7 , 15 , 16 ]. This could explain why, even in otherwise clinically normal pregnancies, we observed a wide range of GA and MGO values.…”
Section: Discussionmentioning
confidence: 99%
“…A ocorrência de restrição de crescimento fetal é reportada entre 7% e 10% dos casos de infecção materna por COVID-19 (Dashraath et al, 2020;Elshafeey et al, 2020). Pesquisas reforçaram ainda que o risco de morbimortalidade perinatal era cerca de duas vezes maior nos recém-nascidos de mães infectadas (Healy, 2021). Quando presentes, os sintomas refletem predominantemente o acometimento do trato respiratório ou a resposta sistêmica à infecção, mas também são observados sintomas gastrointestinais (Brasil, 2021a).…”
Section: Resultsunclassified
“…A multinational study assessing maternal and neonatal morbidity and mortality found that regardless of COVID-19 symptoms, pregnant women were at significantly higher risk of complications and poor pregnancy outcomes, including preeclampsia, eclampsia, preterm birth, intensive care unit admission, and maternal death. Neonatal outcomes were observed to reflect the severity of maternal illness, although lower than maternal risks ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%